2019
DOI: 10.3390/admsci9010006
|View full text |Cite
|
Sign up to set email alerts
|

Evolution to Emergence of Green Buildings: A Review

Abstract: “Green Buildings” are essential in being responsive to the challenges of climate change and global warming while inhibiting natural resources degradation. This demand requires specific attention to increase the adoption of green-certified buildings within the construction industry. Innovative tools and techniques are needed to meet global challenges and strategies set for Sustainable Development Goals of 2030 agenda. This paper provides an intensive review of the evolution of green buildings from a sustainable… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
28
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(28 citation statements)
references
References 56 publications
0
28
0
Order By: Relevance
“…To understand the capillarity of the research on the 2030 Agenda, a first step is to take a look to systematic reviews and bibliometric analyses in the topic. In our research, we have identified 27 reviews so far, where the authors focus on studies of the implementation and the achievement of the SDGs (Barrantes Briceño and Almada Santos, 2019; Guha and Chakrabarti, 2019; Gusmão Caiado et al, 2018; Hristov and Chirico, 2019; Khan et al, 2019; Maroyi, 2018; Merino‐Saum et al, 2018; Omer and Noguchi, 2020; Schiappacasse and Müller, 2018; Zhang et al, 2019), on specific topics and collectives within the Agenda (Baum et al, 2016; Del Pino et al, 2019; Giné‐Garriga et al, 2017; Hartmann et al, 2016; Majinge and Mutula, 2018; Mathez‐Stiefel et al, 2017; Matilla et al, 2018; Simcock and Wittich, 2019; Swamy et al, 2018), on traditional fields of knowledge, now reconsidered in the light of the 2030 Agenda (Elfert, 2019; Rodrigues and Franco, 2019; Storey et al, 2017), and even on contributions to the field of knowledge from researchers in specific regions or countries (Körfgen et al, 2018; Staszkiewicz, 2019).…”
Section: The 2030 Agenda For Sustainable Developmentmentioning
confidence: 99%
“…To understand the capillarity of the research on the 2030 Agenda, a first step is to take a look to systematic reviews and bibliometric analyses in the topic. In our research, we have identified 27 reviews so far, where the authors focus on studies of the implementation and the achievement of the SDGs (Barrantes Briceño and Almada Santos, 2019; Guha and Chakrabarti, 2019; Gusmão Caiado et al, 2018; Hristov and Chirico, 2019; Khan et al, 2019; Maroyi, 2018; Merino‐Saum et al, 2018; Omer and Noguchi, 2020; Schiappacasse and Müller, 2018; Zhang et al, 2019), on specific topics and collectives within the Agenda (Baum et al, 2016; Del Pino et al, 2019; Giné‐Garriga et al, 2017; Hartmann et al, 2016; Majinge and Mutula, 2018; Mathez‐Stiefel et al, 2017; Matilla et al, 2018; Simcock and Wittich, 2019; Swamy et al, 2018), on traditional fields of knowledge, now reconsidered in the light of the 2030 Agenda (Elfert, 2019; Rodrigues and Franco, 2019; Storey et al, 2017), and even on contributions to the field of knowledge from researchers in specific regions or countries (Körfgen et al, 2018; Staszkiewicz, 2019).…”
Section: The 2030 Agenda For Sustainable Developmentmentioning
confidence: 99%
“…To address this issue, the authors point to the utilization of renewable energy technologies based on renewable resources like wind and solar to enhance green growth and achieve ecological sustainable development. However, since the world already hosts considerable CO 2 emissions, the authors propose that technologies like green information systems (Green IS) utilized to reduce CO 2 emissions (Khan et al 2019). In order to coordinate all these elements of the Green ITS, the following section shows the methods and materials involved.…”
Section: Problem Statementmentioning
confidence: 99%
“…The building sector accounts for approximately 40% of global energy consumption [3], and 30% of CO 2 emissions [4]. However, it is recognized that the building sector has great potential to reduce its energy consumption by implementing measures to improve its energy efficiency [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, there has been a large development of green buildings and their implementation is increasingly widespread in many countries [5]. An extensive review of this development can be found in Ahmad et al [7].…”
Section: Introductionmentioning
confidence: 99%